The Relationship Between Breastfeeding History And Age At Menopause With Breast Cancer Incidence In The Oncology Surgery Room Of Jenderal Ahmad Yani Hospital Metro City - Annisa Dwi Rachmawati; Sadiman Sadiman; Elisa Murti Puspitaningrum (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Kanker payudara merupakan kanker yang menempati peringkat pertama sebagai jenis kanker yang paling sering terjadi pada perempuan di seluruh dunia. Kanker payudara menjadi urutan 2 teratas dengan presentasi kasus 11,6% atau 2.296.480 wanita yang didiagnosis menderita kanker payudara, (WHO, 2022). Penyebab kanker payudara sampai saat ini belum diketahui secara pasti namun, ada faktor risiko yang meningkatkan kemungkinan kanker payudara. Dampak kanker payudara meliputi aspek fisik, psikologis, sosial, ekonomi, dan spiritual, termasuk risiko penyebaran ke organ lain serta menjadi penyebab kematian. Tujuan umum penelitian ini untuk mengetahui hubungan antara riwayat menyusui dan usia menopause dengan kejadian kanker payudara pada wanita di Ruang Bedah Onkologi RSUD Jenderal Ahmad Yani Kota Metro. Penelitian ini merupakan penelitian case control. Populasi kasus adalah semua pasien wanita yang terdiagnosa kanker payudara yang ada di ruang bedah onkologi, populasi kontrol semua pasien wanita yang tidak terdiagnosis kanker payudara di ruang bedah onkologi, dengan sampel penelitian berjumlah 68 responden yang terdiri dari 34 sampel kasus dan 34 sampel kontrol. Analisis menggunakan uji chi-square dengan menentukan tingkat kepercayaan 95%. Hasil penelitian didapatkan proporsi wanita dengan riwayat menyusui berisiko 35,5%, dan proporsi wanita dengan usia menopause berisiko 33,8%. Ada hubungan antara riwayat menyusui dengan kanker payudara nilai p-value = 0,005. Ada hubungan antara usia menopause dengan kanker payudara nilai p-value = 0,040. Kata Kunci: Kanker payudara; riwayat menyusui; usia menopause ABSTRACT Breast cancer is the most commonly diagnosed cancer among women worldwide. It ranks as the second most prevalent cancer overall, accounting for 11.6% of all cases, with approximately 2,296,480 women diagnosed in 2022 (WHO, 2022). Although the exact cause of breast cancer remains unclear, several risk factors have been identified that increase the likelihood of its occurrence. The impact of breast cancer extends across physical, psychological, social, economic, and spiritual domains, including the risk of metastasis to other organs and its contribution to mortality. The general objective of this study was to examine the relationship between breastfeeding history and age at menopause with breast cancer incidence in the oncology surgery room of Jenderal Ahmad Yani Hospital Metro City. This study employed a case-control design. The case population consisted of all female patients diagnosed with breast cancer in the oncology surgical ward, while the control population included female patients without a breast cancer diagnosis in the same ward. A total of 68 respondents were included, comprising 34 cases and 34 controls. Data were analyzed using the chi-square test with a 95% confidence level.The results showed that 35.5% of women had a high-risk breastfeeding history, and 33.8% had a high-risk age at menopause. A significant association was found between breastfeeding history and breast cancer incidence (p-value = 0.005). In addition, age at menopause was also significantly associated with breast cancer incidence (p-value = 0.040). The findings of this study indicate that there is a significant relationship between breastfeeding history and age at menopause with the incidence of breast cancer. It is recommended that hospitals provide education regarding breast cancer risk factors in order to enhance awareness and contribute to reducing the incidence of breast cancer. Keywords: Breast cancer; breastfeeding history; age at menopause